1959
DOI: 10.1152/ajplegacy.1959.197.6.1333
|View full text |Cite
|
Sign up to set email alerts
|

Transport of vitamin A in vitro across normal isolated rat intestine and intestine subjected to ‘partial’ resection

Abstract: The transport of vitamin A across normal and resected intestine was studied in vitro by the method of Darlington and Quastel. The results showed that under aerobic conditions the rate of transport of vitamin A across normal and resected intestine was identical. In contrast, under anaerobic conditions transport was reduced 50% for resected intestine and totally inhibited for control intestine. These results were duplicated under aerobic conditions when 2, 4, dinitrophenol was added to the mucosal solution. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1963
1963
1987
1987

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Anaerobiosis has been demonstrated in two studies on the absorptive function of intestine 2 months after resection in the rat (8,9). The results showed that whereas absorptive competence for vitamin A was not reduced, anaerobic glycolytic phosphorylation associated with vitamin A absorption was no longer rate limiting in the intestine of resected rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anaerobiosis has been demonstrated in two studies on the absorptive function of intestine 2 months after resection in the rat (8,9). The results showed that whereas absorptive competence for vitamin A was not reduced, anaerobic glycolytic phosphorylation associated with vitamin A absorption was no longer rate limiting in the intestine of resected rats.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the proliferative rate, which occurred equally in all segments of small intestine following resection, persisted long after the total weight of the intestine and its capacity to absorb vitamin A had returned to normal (8,10). An explanation is offered for the persistence of this effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resection of the proximal two-thirds of the small intestine causes the greatest morphological change or "compensatory hypertrophy," with little or no nutritional disturbance to the animal (3,4) while distal resection is associated more with weight loss and malabsorption (4,5), gastric hypersecretion (6), enhanced gastric emptying (7), and reduced intestinal transit time (5,7). Whether proximal or distal factors underlie the reported disturbances in ileal blood flow (8), vitamin A transport (9), or mucosal cell kinetics (10)(11)(12) is still uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some evidence supports the concept that after resection the intestinal mucosa acquires characteristics of metabolic immaturity. Whereas normal rats depend on energy supplied by oxidative phosphorylation in order to transport vitamin A, resected animals utilize the energy supplied by anaerobic glycolytic phosphorylation (28). Similarly, Weiser and Hernandez (7) found that when glucose transport was measured in everted gut sacs as a function of weight of the segment, there was a decrease in capacity of glucose transport in segments from distally resected animals.…”
Section: Discussionmentioning
confidence: 98%